Muslim comics and warscape witnessing - Santesso, Esra Mirze (Studies in comics and cartoons, 2023)
Recent decades have seen an unprecedented number of comics by and about Muslim people enter the global market. Now, Muslim Comics and Warscape Witnessing offers the first major study of these works. Esra Mirze Santesso assesses Muslim comics to illustrate the multifaceted nature of seeing and representing daily lives within and outside of the homeland. Focusing on contemporary graphic narratives that are primarily but not exclusively from the Middle East—from blockbusters like Marjane Satrapi’s Persepolis to more local efforts such as Leila Abdelrazaq’s Baddawi—Santesso explores why the graphic form has become a popular and useful medium for articulating Muslim subjectivities. Further, she shows how Muslim comics "bear witness" to a range of faith-based positions that complicate discussions of global ummah or community, contest monolithic depictions of Muslims, and question the Islamist valorization of the shaheed, the "martyr" figure regarded as the ideal religious witness. By presenting varied depictions of everyday lives of Muslims navigating violence and militarization, this book reveals the connections between religious rituals and existence in warscapes and invites us to more deeply consider the nature of witnessing itself.